Split equality variational inequality problems for pseudomonotone mappings in Banach spaces - BOIKANYO, Oganeditse A.; ZEGEYE, Habtu (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
A new algorithm for approximating solutions of the split equality variational inequality problems (SEVIP) for pseudomonotone mappings in the setting of Banach spaces is introduced. Strong convergence of the sequence generated by the proposed algorithm to a solution of the SEVIP is then derived without assuming the Lipschitz continuity of the underlying mappings and without prior knowledge of operator norms of the bounded linear operators involved. In addition, we provide several applications of our method and provide a numerical example to illustrate the convergence of the proposed algorithm. Our results improve, consolidate and complement several results reported in the literature. Mathematics Subject Classification (2010): 47H09, 47J20, 65K15, 47J05, 90C25.